Is Streamer Trust the Key to Impacting Purchase Intentions in Live Fashion Streaming? - Restu, Neng (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Digital transformation has profoundly reshaped consumer shopping behaviors, making live streaming social commerce a prominent trend. Despite its rapid growth, we still have a limited understanding of how streamer characteristics influence purchase intention, particularly for fashion products. The combined roles of trust and viewing intention in this context are also not fully explored. This study uses the Stimulus-Organism-Response (SOR) framework to investigate how streamer interactivity and attractiveness affect purchase intention. It specifically examines whether trust mediates this relationship and if intention to watch moderates it. Data was collected from 158 users of live streaming fashion products through an online survey and analyzed using PLS-SEM. The results show that both streamer interactivity and attractiveness significantly impact trust and purchase intention. Trust fully mediates the effect of streamer characteristics on purchase intention. Additionally, intention to watch significantly moderates the relationship between interactivity and purchase intention. All hypothesized relationships were statistically significant (p<.05). The model also demonstrated strong predictive power, with an R2 of 0.702 for purchase intention and 0.56 for streamer trust. This research enriches marketing literature by highlighting the critical roles of interaction and trust in live streaming content for boosting purchase intention. It offers valuable insights for businesses, though the findings are limited to fashion products on specific social commerce platforms.